The role of strobilanthes crispus active fraction (f3) on glucose metabolism of MDA-MB-231 breast cancer cell line - Muhammad, Siti Nur Hasyila (2023)
MDA-MB-231 is a triple negative breast cancer cell (TNBC) that represents breast cancer with a poor prognosis and limited treatment options. Since TNBCs exhibit increased glycolysis, cancer metabolism may become a great target for its anticancer therapy. Strobilanthes crispus (S.crispus), a plant native to tropical Asian countries, is well-known for its medicinal properties. S.crispus extract has been shown to have promising anticancer properties. The purpose of this study is to determine the effect of S. crispus active fraction (F3) and its bioactive compounds (lutein, β- sitosterol, and stigmasterol) on glucose metabolism of MDA-MB-231 cells. The 3- [4,5-dimethylthiazol-2-yl]-2,5 diphenyl tetrazolium bromide (MTT) assay showed anti-proliferative activities of F3 and its bioactive compounds with IC50 values of 100 μg/mL (F3), 20 μM (lutein), 25 μM (β-sitosterol), and 90 μM (stigmasterol) in MDAMB- 231 cells after 48 h. The IC50 value of each compound was then used in subsequent assays. A fluorescence spectrophotometer was used to quantify glucose uptake activity and lactate concentration in treated MDA-MB-231 cells. Our findings demonstrated that F3 and its bioactive compounds reduced the uptake of glucose into MDA-MB- 231 cells, except for stigmasterol. However in comparison with controls, lactate concentration was significantly reduced in all treated MDA-MB-231 cells. Interestingly, the presence of F3 and its bioactive compounds had no effect on the glycolytic activities of non-malignant breast cell line (MCF10A), indicating that the treatments were safe for normal cells. The expression and localisation of GLUT1 were then determined using Western blot and fluorescence microscopy. Despite the inhibition of glucose uptake, no decrease in GLUT1 expression was observed in the treated cells. Instead, F3, lutein, and β-sitosterol inhibited GLUT1 localisation from the cytoplasm to the cell membrane. The findings were supported by reduced PKC activity after the same treatments measured by spectrophotometer, and increased TXNIP protein expression as detected by Western blot. The PI3K/AKT/mTOR/HIF1α pathway is known to regulate metabolism in cancer cells. Hence, the effects of F3 and its bioactive compounds on the expression of AKT, pAKT, mTOR and HIF1α proteins were determined using flow cytometry analysis, and downregulation of those proteins was observed in all treated MDA-MB-231 cells. Anti-metastatic activity was also induced by F3 and its bioactive compounds in TNBCs, as demonstrated by a decrease in both migration (assayed using transwell migration assay) and fibronectin expression. As a conclusion, anti-glycolytic and anti-metastatic activities in MDAMB- 231 cells induced by F3 are attributed to the inhbition of the AKT/mTOR/HIF1α signalling pathway by its bioactive compounds.